Evaluation of mechanical properties of glued elements for model kits - M. L. Kalinichenko; B. M. Nemenenok; A. N. Grigorchik (Литьë и металлургия)
The work is devoted to assessing the quality of fastening the abrasive component to the metal base by gluing on the example of a clutch disc. An assessment of the operability of the patented technique for testing for conditional shear of glued joints is given. The paper proposes a method of using foamed materials to create one‑time or single model kits for the production of missing parts for mechanical engineering.